Compressibility, turbulence and high speed flow - Gatski, T. B; Bonnet, Jean-Paul, 1949- (Oxford : Academic Press, 2013)
Compressibility, Turbulence and High Speed Flow Second Edition, An introduction to compressible turbulent flows and compressible turbulence, with state-of-the-art measurement and analysis techniques, Compressibility, Turbulence and High Speed Flow introduces the reader to the field of compressible turbulence and compressible turbulent flows across a broad speed range, through a unique complimentary treatment of both the theoretical foundations and the measurement and analysis tools currently used. The book provides the reader with the necessary background and current trends in the theoretical and experimental aspects of compressible turbulent flows and compressible turbulence. Detailed derivations of the pertinent equations describing the motion of such turbulent flows is provided and an extensive discussion of the various approaches used in predicting both free shear and wall bounded flows is presented. Experimental measurement techniques common to the compressible flow regime are introduced with particular emphasis on the unique challenges presented by high speed flows. Both experimental and numerical simulation work is supplied throughout to provide the reader with an overall perspective of current trends. Key features include: An introduction to current techniques in compressible turbulent flow analysis, An approach for engineers to identify and solve complex compressible flow challenges, Prediction methodologies, including the Reynolds-averaged Navier Stokes (RANS) method, scale filtered methods and direct numerical simulation (DNS), Current strategies focusing on compressible flow control Book jacket
Includes bibliographical references and index
Keywords: Turbulence -- Mathematical models; Compressibility